Avalia????o da morfologia facial, contatos oclusais e atividade eletromiogr??fica de m??sculos mastigat??rios em adolescentes com e sem disfun????o temporomandibular. - Lauriti, Leandro (2011)
The aim of this observational cross-sectional was to evaluate the association between facial morphology, type of occlusion, number of occlusal contacts and electromyographic activity of masticatory muscles in adolescents with temporomandibular disorders (TMJ). We assessed adolescents between 14 and 18 years for both genders of an institute of education. All participants, we applied the index Helkimo for the classification of TMD. Clinical examination was performed and the children were classified into Group without TMD; Group TMD Light, Group TMD Moderate and Group TMD Severe. We obtained the type of occlusion and for the record of the contact points we used carbon strips. We conducted standardized photographs for analysis of facial morphology. Then, participants with and without TMD were submitted to electromyographic evaluation of masticatory muscles at rest, habitual chewing and maximum intercuspation. Statistical analysis used the chi-square and Fisher exact test for evaluation of categorical variables for comparison of means t-test and analysis of variance (ANOVA), complemented by the LSD test and correlation between continuous variables were analyzed by Pearson correlation test, adopting a significance level of p ??? 0.05. It was concluded that the DTM was more prevalent in adolescent females, and the headache of the most prevalent symptoms. The number of occlusal contacts and facial pattern did not differ significantly between the groups with and without DTM. The electromyographic activity of masticatory muscles were greater in adolescents with TMD Moderate / Severe at rest and during chewing compared to those without TMJ.